Mediatisasi Politik dan Perilaku Pemilih: Penggunaan Google Trend Sebagai Metode Alternatif Memprediksi Kemenangan Kandidat - Eric Fernardo (JURNAL LENSA MUTIARA KOMUNIKASI, 2022)
In 2020, Indonesia has held simultaneous regional head elections which held governor elections in 9 provinces, mayor elections in 37 cities and regent elections in 224 regencies. Candidates in general elections often use surveys as a reference in estimating their potential for victory, even though to conduct popularity, acceptability and electability surveys require a high level of validity and reliability, for this reason, a large survey team is needed in distributing questionnaires and large funds for operational needs, so it is necessary to develop alternative methods of data collection in predicting candidate winner, other than survey methods. Google Trend as a service from Google that provides site search statistics by displaying the popularity of keyword within a certain time range where statistical results can be displayed by region has the potential to be an alternative method to surveys. In several previous studies in the United States and Canada, Google Trend managed to correctly predict the winner of the presidential election in the US and the winner of the election in Canada. This research fills a gap in the Indonesian context to see the accuracy of Google Trend in predicting the winner of the governor election in 9 provinces in the simultaneous regional elections in 2020. As a result, Google Trend succeeded in predicting the victory of candidates in Jambi, Central Kalimantan, North Sulawesi, West Sumatra; while doubtful in Bengkulu and South Kalimantan; and Google Trend is not accurate in predicting in North Kalimantan, Riau Islands and Central Sulawesi. Google Trend's lack of accuracy in predicting the governor's candidate victory in Indonesia is allegedly because Google Trend's services in Indonesia have not reached the district/district level compared to the United States and Canada which have reached the district/sub-district level. In addition, as an alternative method, there are a number of important notes for Google Trend because it has not been able to distinguish the tone of news whether it is positive or negative because Google Trend is still focused on the number of keyword searches that are most sought after by users, even though the tone of the news is important to see public sentiment.